Penerapan Metode Eselon Baris Tereduksi pada Rekayasa Volume Lalu Lintas - Tetty Natalia Sipayung; Inne Kristina Gulo (Universitas Majalengka, 2023)
Traffic congestion is one of the problems of land transportation and is the center of attention, especially for traffic users in big cities. Through a literature study using a descriptive method, a study was carried out with the aim of estimating the traffic volume at each intersection of two groups of connected and intersecting one-way roads. The initial step of this study is to conduct a literature review and provide some of the necessary definitions. Second, make the formulation of traffic volume engineering problems. Third, determine the variables and make assumptions. There are four variables involved. Fourth, form a mathematical model. The resulting model is in the form of a system of non-homogeneous linear equations. Fifth, determine the solution and interpretation of the model. The model is interpreted in the form of an enlarged matrix and through the application of the reduced row echelon method the result is that the system is consistent and has a rank of three. Sixth, implementation with the help of MATLAB. Seventh, drawing conclusions. Through this study, it was concluded that the volume of the number of vehicles in the three lanes depends on one other lane.